(untitled) (Филолошке студије, 2019)
Stef Jansen’s book Antinationalism offers an analysis of the resistance to nationalism in post-Yugoslav countries, primarily in Croatia and Serbia, realizing primarily that it is the rural communities where these extreme national sentiments took hold. Jansen proceeds to explain how, in his view, there is an intrinsic type of Saidian orientalism common to the urban centres, in which the rural is presented as primitive and backwards. Though Jansen himself offers both a number of academic resources, scientific and philosophical in origin, as well as own research as proof that the nationalism promoted by Tudjman and Milosevic did stem from the rural communities primarily, he sees the urban resistance to the rural as something that, in his own words, ’irritates’ him, as he notices the ’lack of tolerance’ of the socium which tries to fight the intolerant nationalistic views of the world. The essay shows that in addition to clear subjective bies, Jansen falls prey to a rather common, yet unnoticed logical fallacy that plagues modern liberal/leftist discourse – the fallacy of the excluded middle (the fallacy of false dychotomy), thus distoring liberal discourse and leading into pseudoliberalism.